Brazilian Astronomy Olympiad of High School: texts and contexts (Research, Society and Development, 2020)
The study of astronomy in high school is approached both by national curriculum guidelines and by researchers in the field of science education. The curricular parameters and guidelines (PCNEM, PCN+ and OCEM), for example, point out that the teaching of Astronomy in Schools must be carried out in a contextualized manner and in dialogue with the student's daily life. The Brazilian Astronomy of Olympiad (OBA) presents itself as an important contribution, awakening and motivating students to teach scientific topics. This research analyzed how the alignment between the high school OBA tests has occurred and the indications proposed by official documents cited. Based on a qualitative approach, of an exploratory nature, we adopted Content Analysis as a way to analyze the high school OBA exams. The results revealed some points of convergence between the guidelines of the official documents and the OBA issues. The presence of everyday actions has been more constant in its last editions, involving concepts that permeate different areas of knowledge. This fact promotes more attractive questions for students, moving away from the mechanization of teaching, being a contribution for the teacher to approach astronomy with the students.